Identity processing styles and cell phone addiction: The mediating role of religious coping - Ghasem Askarizadeh; Maryam Poormirzaei; Reyhane Hajmohammadi (Shahid Beheshti University of Medical Sciences, 2017)
Background and Objectives: The aim of this study was to investigate the mediating role of religious coping in the relationship between identity processing styles and cell phone addiction. For downloading the full-text of this article please click here. Materials & Methods: This descriptive and correlational study encompassed all students in Zahedan University in 2016 as its research population. From this population, 384 were selected using simple random sampling by Krejcie Morgan Table. Questionnaires of  Identity processing styles, religious coping and addiction to cell phones were used for data collection. For data analysis, SPSS 19 was used for descriptive statistics and Pearson correlation coefficient and LISREL 8.50 software was used for structural equation modeling (path analysis). In this study, all relevant ethical issues were considered. Results: Results showed that there is a positive significant correlation between cell phone addiction with diffuse-avoidant style (p≤0/01) and negative religious coping (p≤0/05). The relationship between negative religious coping with informational and normative styles is negative and with diffuse-avoidant style is positively meaningful (p≤0/01). Path analysis supported the mediating role of negative religious coping in the relationship between normative and diffuse-avoidant identity processing styles with cell phone addiction. Conclusion: The results of this study indicated that negative religious coping has restricted mediating role in the relationship between identity processing styles and cellphone addiction. Keywords: Cell phone addiction, Identity processing styles, Religious coping For downloading the full-text of this article please click here. Please cite this article as: Askarizadeh Gh, Poormirzaei M ,Hajmohammadi R. Identity processing styles and cell phone addiction: The mediating role of religious coping. J Res Relig Health.2017;3(1):18- 29.